Diabetes Mellitus, Preoperative Glycemic Control and Postoperative Outcomes: A Multi-Ethnic Asian Perspective - Roderica Rui Ge Ng; Charlene Xian Wen Kwa; Yuhe Ke; Brenda Pei Yi Tan; Mengling Feng; Hairil Rizal Abdullah (Clinical Medicine Insights: Endocrinology and Diabetes)
Background: Diabetes mellitus (DM) is a critical risk factor associated with postoperative complications. Preoperative glycemic control, commonly assessed by glycated hemoglobin (HbA1c), may help stratify patients with DM. However, association between DM, HbA1c levels and perioperative outcomes in multi-ethnic Asian populations with distinct cardiometabolic profiles remains underexplored. Objectives: This study aimed to study the association between pre-existing DM, suboptimal glycemic control (HbA1c ≥ 7%), and postoperative complications in elective non-cardiac surgical patients, focusing on the role of HbA1c as a risk stratification tool. Methods: This secondary analysis included 688 patients from a prospective cohort at Singapore’s largest tertiary hospital. Postoperative complication(s) were assessed using the Comprehensive Complication Index. Patients were categorized into 2 groups—DM (regardless of HbA1c) and no DM (HbA1c ≤ 6%). We used multivariable logistic regression to explore associations within the entire cohort and DM subgroup. The relationship between preoperative HbA1c levels and postoperative complication(s) was also explored. Results: The overall incidence of postoperative complication(s) was 20.78%. DM was independently associated with increased postoperative complication(s) (adjusted OR 2.57, 95% CI 1.20-5.50, P = .015). A trend toward a higher likelihood of postoperative complication(s) was observed in patients with DM and suboptimal glycemic control (adjusted OR 1.39, 95% CI 0.56-3.45, P = .482) though this did not reach statistical significance. A noteworthy U-shaped relationship was identified between preoperative HbA1c levels and postoperative complication(s), with increased complications at both low and high HbA1c levels. Conclusion: This study highlights a significant association between DM and increased postoperative complications. The observed U-shaped relationship between HbA1c levels and complications underscores the need for comprehensive risk assessment across the full glycemic spectrum. Routine HbA1c screening and tailored perioperative strategies in multi-ethnic Asian populations could enhance surgical outcomes, reduce healthcare costs, and support broader public health goals in DM management.